2015
DOI: 10.1186/s40064-015-1050-3
|View full text |Cite
|
Sign up to set email alerts
|

The aspect of experience in ultra-triathlon races

Abstract: Previous experience seems to be an important predictor for endurance and ultra-endurance performance. The present study investigated whether the number of previously completed races and/or the personal best times in shorter races is more predictive for performance in longer non-stop ultra-triathlons such as a Deca Iron ultra-triathlon. All female and male ultra-triathletes who had finished between 1985 and 2014 at least one Double Iron ultra-triathlon (i.e. 7.6 km swimming, 360 km cycling and 84.4 km running),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… Single case study, female non-athlete, training from sedentary lifestyle to ultra-event [ 28 ] 24 h time-limited, self-paced road race events 2022 Single case study of the biophysical characteristics of a male ultra-cyclist with two world records in ultra-cycling events [ 57 ] Cape Argus Cycling Tour and Cape Epic 2012 Differences between mountain bikers and road cyclists in ultra-races in terms of motivation to participate and behavior [ 55 ] Ultra-triathlons Double, Triple, and Deca Iron 1985 to 2009 Increase in overall number of finishers for Double (360 km cycling) and Triple (540 km cycling) races, Deca (1,800 km cycling) finishers stable, women relatively slower than men with increasing length [ 42 ] Triple Iron races vs. ultra-marathon races 2007–2009 Cyclists participating in triple triathlons (540 km cycling) are younger, have a higher training volume, and have higher body mass than runners [ 44 ] Ironman and Triple Ironman races 2007–2009 Ironman participants vs. Triple Ironman (540 km cycling) participants, 49 different nationalities, ultra-athletes with higher BMI, shorter stature, and larger training volume [ 45 ] Double Iron ultra-triathlon 1985–2010 European participants in ultra-triathlons (360 km cycling) have faster finishing times than North American athletes [ 50 ] Ultra-triathlon races 1985–2014 Influence of experience on performance in longer ultra-triathlons (360 km, 540 km, 900 km, or 1,800 km cycling) [ 47 ] Triple Iron ultra-triathlon races 1988–2011 Proportionally more of the female participants finished triple iron ultratriathlons (540 km cycling) than of the male participants, race time...…”
Section: Resultsmentioning
confidence: 99%
“… Single case study, female non-athlete, training from sedentary lifestyle to ultra-event [ 28 ] 24 h time-limited, self-paced road race events 2022 Single case study of the biophysical characteristics of a male ultra-cyclist with two world records in ultra-cycling events [ 57 ] Cape Argus Cycling Tour and Cape Epic 2012 Differences between mountain bikers and road cyclists in ultra-races in terms of motivation to participate and behavior [ 55 ] Ultra-triathlons Double, Triple, and Deca Iron 1985 to 2009 Increase in overall number of finishers for Double (360 km cycling) and Triple (540 km cycling) races, Deca (1,800 km cycling) finishers stable, women relatively slower than men with increasing length [ 42 ] Triple Iron races vs. ultra-marathon races 2007–2009 Cyclists participating in triple triathlons (540 km cycling) are younger, have a higher training volume, and have higher body mass than runners [ 44 ] Ironman and Triple Ironman races 2007–2009 Ironman participants vs. Triple Ironman (540 km cycling) participants, 49 different nationalities, ultra-athletes with higher BMI, shorter stature, and larger training volume [ 45 ] Double Iron ultra-triathlon 1985–2010 European participants in ultra-triathlons (360 km cycling) have faster finishing times than North American athletes [ 50 ] Ultra-triathlon races 1985–2014 Influence of experience on performance in longer ultra-triathlons (360 km, 540 km, 900 km, or 1,800 km cycling) [ 47 ] Triple Iron ultra-triathlon races 1988–2011 Proportionally more of the female participants finished triple iron ultratriathlons (540 km cycling) than of the male participants, race time...…”
Section: Resultsmentioning
confidence: 99%
“…can have very different environmental conditions than swimming in a pool, where most athletes train, and these differences can make triathlon training experience especially important for swimming performance. Previous studies have already demonstrated the positive impact of previous experience on performance in the triathlon's total race time [20,21]. In the same direction, sports practice during childhood, even non-specific physical activity, has previously been shown to be highly correlated to better performances in swimming and total race times in the Olympic triathlon [24].…”
Section: Predictors Of Triathlon Overall and Split Race Times For The...mentioning
confidence: 89%
“…Triathlon experience appears to be an important variable in predicting performance for female athletes, as evidenced by the prediction equations for swimming split time and overall race time. Moreover, previous research has shown that triathlon experience is an important predictor of performance in splits, particularly in swimming and total race time [9,[20][21][22][23]. Swimming in the sea, bay, lake, or river (current, temperature, navigation, buoyancy, etc.)…”
Section: Predictors Of Triathlon Overall and Split Race Times For The...mentioning
confidence: 99%
“…Successful finishers in the “TransEurope FootRace” 2009 showed that the extent of pre-race training in the last year before the race and personal best times for marathon and specific ultra-marathons have a high correlation to race performance ( 49 ). In ultra-triathletes competing in x-times the Ironman-distance triathlons, previous experience (i.e., fast personal best times of shorter races) seemed important in performance for longer ultra-triathlon races ( 51 ). Based on the power metrics, the cyclist could produce more power per kilogram (about 5% more).…”
Section: Discussionmentioning
confidence: 99%